2009
DOI: 10.3329/jhpn.v27i3.3377
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Self-reported Acute Gastrointestinal Illness in Cuba

Abstract: Acute gastrointestinal illness is an important public-health issue worldwide. Burden-of-illness studies have not previously been conducted in Cuba. The objective of the study was to determine the magnitude, distribution, and burden of self-reported acute gastrointestinal illness in Cuba. A retrospective, cross-sectional survey was conducted in three sentinel sites during June-July 2005 (rainy season) and during November 2005-January 2006 (dry season). Households were randomly selected from a list maintained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…also found a similar estimate of 7% for infectious gastrointestinal illness among respondents in Australia ( 15 ). In contrast, other studies in the USA ( 10 , 11 ) (July 1996–June 1997 and July 1998–June 1999), Canada ( 13 , 14 , 19 ), Queensland ( 29 ), and Cuba ( 8 ) found much higher estimates (8.6-15.5%) of acute diarrhoea compared to that in our study. In Malta, the rate for infectious intestinal disease was slightly lower than that of ours (3.2%) ( 21 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…also found a similar estimate of 7% for infectious gastrointestinal illness among respondents in Australia ( 15 ). In contrast, other studies in the USA ( 10 , 11 ) (July 1996–June 1997 and July 1998–June 1999), Canada ( 13 , 14 , 19 ), Queensland ( 29 ), and Cuba ( 8 ) found much higher estimates (8.6-15.5%) of acute diarrhoea compared to that in our study. In Malta, the rate for infectious intestinal disease was slightly lower than that of ours (3.2%) ( 21 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies in Argentina, the USA, Malta, and Australia also did not find any differences between the sexes ( 7 , 10 , 11 , 21 , 29 ). In Cuba however, males had higher morbidity due to acute gastrointestinal disease than females ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Municipal surveillance data for Gálvez support the seasonal trend observed in this study; during the same timeframe, surveillance data showed a peak of GI prevalence in the high season (Phase 1) that was approximately three times the prevalence seen in the low season (Phase 2). A seasonal effect was also observed in a Cuban study in 2005–2006, where the prevalence of GI was approximately 2–5 fold greater in the rainy season compared to the dry season ( 10 ). Likewise, in Gálvez, the high season of GI coincided with more rainfall, and the low season of GI coincided with less rainfall [Oliveros Weather Station, Santa Fe, Argentina, Instituto Nacional de Tecnología Agropecuaria.…”
Section: Discussionmentioning
confidence: 59%
“…However, it was striking that, in Phase 1 (but not Phase 2), all cases aged less than15 years were male (n=8, data not shown). Similarly, results of a Cuban study indicate that, when controlling for season, sentinel site, and age-group, there was a higher risk for males than for females, supporting this potential relationship ( 10 ). A study in England and Wales on demographic determinants of Campylobacter -associated infections also found an increased risk among males between birth and 17 years of age ( 27 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation